An empirical study of the dividend-adjusted black-scholes model - Lum, Chiew Yuen (2014)
As the stock options market of Singapore is still very young, being re-launched only on 8 March 1993, few researches have been conducted on this market. The purpose of this study is to test the significance of dividend adjustments in pricing options using the Black-Scholes Model.